ADAMTS‐13 activity and ischemic heart disease: a Mendelian randomization study. (3rd October 2018) - Schooling, C. M.; Luo, S.; Johnson, G.
Abstract: Essentials Cardiovascular disease remains the leading cause of global mortality despite progress in control. We assessed the role of ADAMTS‐13 in ischemic heart disease using Mendelian randomization. Genetically instrumented ADAMTS‐13 activity reduced ischemic heart disease. Therapeutics targeting ADAMTS‐13 activity could perhaps be repurposed in ischemic heart disease. Background: Despite great progress in the prevention and control of cardiovascular disease, it remains the leading cause of global mortality and morbidity, with new unexpected risk factors emerging and few effective new pharmaceutical treatments. ADAMTS‐13 is involved in a clotting disorder, thrombotic thrombocytopenic purpura, for which new treatments are being developed. Observationally, ADAMTS‐13 activity is inversely associated with ischemic heart disease (IHD) but positively associated with diabetes. Objectives: To obtain unconfounded estimates of the effect of ADAMTS‐13 on IHD, diabetes and lipids. Methods: We applied genetic variants strongly, ( P < 5 × 10 −8 ), solely and independently associated with ADAMTS‐13 to the largest available extensively genotyped case–control studies of IHD and diabetes and to a large study of lipids to obtain Mendelian randomization inverse variance weighted (IVW) estimates. Sensitivity was evaluated through weighted median and MR‐Egger estimates. Results: Genetically predicted ADAMTS‐13 activity, based on three genetic variants, was consistently inversely associated with IHD (IVW odds ratio [OR] 0.91 per effect size; 95% confidence interval [CI] 0.86–0.97) but not with diabetes (OR 0.94, 95% CI 0.88–1.01) or high or low‐density lipoprotein cholesterol (0.01, 95% CI −0.02 to 0.04; −0.01, 95% CI −0.04 to 0.02, respectively). ADAMTS‐13 antigen, based on four genetic variants, was not associated with any outcome. Conclusions: This genetic validation of ADAMTS‐13 activity as a target of intervention in IHD raises the possibility of new ways of prevention and treatment being developed by repurposing therapeutics that raise ADAMTS‐13 activity, or by other environmental or dietary interventions that raise ADAMTS‐13 activity.